Effects of dietary nutrient levels on microbial community composition and diversity in the ileal contents of pregnant Huanjiang mini-pigs. - Yujiao Ji; Xiangfeng Kong; Huawei Li; Qian Zhu; Qiuping Guo; Yulong Yin (PLoS ONE, 2017)
The mammalian gut microbiota influences various metabolic and physiological processes. Substantial metabolic changes occur during a healthy pregnancy that may be related to microbiota composition dynamics. However, the effect of diet on intestinal microbiota composition and diversity during pregnancy remains unclear. We examined the ileal contents of Huanjiang mini-pigs at two pregnancy stages to determine the effects of dietary nutrient levels on such microbial communities. Animals received either a higher-nutrient (HN) diet formulated to meet US National Research Council requirements or a lower-nutrient (LN) diet that met the Chinese National Feeding Standard recommendations. On day 45 or 75 of pregnancy, sows were euthanized and their ileal contents sampled. Experimental diet and pregnancy stage did not affect ileal bacterial richness or diversity, as determined by Chao1 and ACE species richness measures and Shannon and Simpson indices, respectively. The phyla Firmicutes and Proteobacteria, accounting for 69.99-85.44% and 5.82-15.17% of the total reads, respectively, predominated regardless of diet. At the genus level, diet significantly affected the abundance of Lactobacillus species, which was greater in pigs given HN feed (P < 0.05), but had little impact on that of Megasphaera species (P = 0.096). Pregnancy stage had a minimal effect on Proteobacteria numbers (P = 0.053). The number of bacteria of the phylum Firmicutes and genus Lactobacillus decreased, while that of the phylum Proteobacteria, family Enterobacteriaceae, and genus Bacteroides increased between days 45 and 75 of pregnancy. Of the short-chain fatty acids (SCFAs) measured, only propionate levels changed significantly, with higher concentrations observed on day 45 than on day 75. Our findings indicate that Firmicutes and Proteobacteria dominate pregnant sow ileal bacterial profiles. Excepting a tendency for the number of Proteobacteria to increase as pregnancy progressed, pregnancy stage and diet had little effect on ileal microbiotic composition and diversity and luminal SCFA concentrations.